(Des)memória e catástrofe: considerações sobre a literatura pós-golpe de 1964 - Ettore Finazzi-Agrò (Estudos de Literatura Brasileira Contemporânea, 2014)
The text aims to rethink, in the wake of an established critical tradition, the role of literature in the representation and complaint of acts of repression carried out by the Brazilian military regime since 1964, and with greater forcefulness and strength, since 1968, after enactment of Institutional Act n. 5. In this context, the stories – told by many authors and some of the survivors of repression – seem to play an important role in supplying the deficiencies of the History, in order to show, effectively even if through fiction, the nefas that characterized in particular torture and murder of opponents. The status of literature – his ability to say what is forbidden to historiography, the possibility of recreating the real through imagination – drove, in fact, many writers to witness the horror and violence that marked the regime established in Brazil fifty years ago, even giving us the “physical” representation of pain and blood generated by a power acting in a “state of exception”.